Managing forensic DNA records in a divided world: the Belgian case. (16th November 2015) - Jeuniaux, Patrick P.J.M.H.; Renard, Bertrand; Duboccage, Leen; Steuve, Séverine; Stappers, Caroline; Gallala, Inès; De Moor, Sabine; Jonckheere, Alexia; Mine, Benjamin; Vanhooydonck, Beatrijs; Kempenaers, Morgane; De Greef, Christine; et al.
Abstract : Purpose: – This paper aims to describe the activity of managing records related to forensic DNA identification. First, it illustrates the fundamentals behind the technique of forensic DNA identification. Second, it explains the legal and institutional contexts in which it is used as well as the notion of DNA-based judicial records. Third, it provides details of records management issues that are met in practice. Design/methodology/approach: – An interdisciplinary team reflects upon the practices surrounding the management of DNA-based records in the Belgian National DNA database during more than 10 years. Findings: – The main problems with managing DNA-based judicial records stem from the existence of natural boundaries between the various stakeholders operating with or within the Belgian judicial system. Six types of issues have been found: non-automaticity and omission, error-prone and inefficient manual operations, electronic issues, results quality, useful reporting and incoherence and duplication. These problems are discussed in terms of four records characteristics: completeness, correctness, traceability and usability. Research limitations/implications: – The research is limited to the Belgian case with no comparison with other countries. Practical implications: – This paper attempts to formulate general principles that aim to stimulate good practices in managing records in the field of criminal justice. Social implications: – The ethical issues surrounding the domain of criminal policy (e.g. the proper use of financial resources, the fair and balance use of records to carry out justice) are of general interest to the public. Originality/value: – The paper benefits from a large temporal angle (more than 10 years) and applies a multidisciplinary viewpoint on its subject.